2013
DOI: 10.4085/1062-6050-48.1.04
|View full text |Cite
|
Sign up to set email alerts
|

Practices of Weight Regulation Among Elite Athletes in Combat Sports: A Matter of Mental Advantage?

Abstract: Context The combination of extensive weight loss and inadequate nutritional strategies used to lose weight rapidly for competition in weight-category sports may negatively affect athletic performance and health. Objective To explore the reasoning of elite combat-sport athletes about rapid weight loss and regaining of weight before competitions. Design Qualita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
118
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(120 citation statements)
references
References 39 publications
1
118
0
1
Order By: Relevance
“…A uniform message is needed that stresses that this protocol must be considered as part of the old, unhealthy training style. Indeed, several studies have shown that these behaviors reduce the wrestler's physical and technical abilities to compete [30][31][32] . If changes in mentality are not achieved through education, it will be hard to change these unhealthy patterns because they are seen as an inherent part of the sport.…”
Section: Discussionmentioning
confidence: 99%
“…A uniform message is needed that stresses that this protocol must be considered as part of the old, unhealthy training style. Indeed, several studies have shown that these behaviors reduce the wrestler's physical and technical abilities to compete [30][31][32] . If changes in mentality are not achieved through education, it will be hard to change these unhealthy patterns because they are seen as an inherent part of the sport.…”
Section: Discussionmentioning
confidence: 99%
“…Although not all studies reported that weight loss is associated with competitive success, none reported that weight loss is associated with less success, rendering RWL to be either beneficial or not harmful to competitive performance. Other than the physical advantages, there is evidence that RWL may also confer mental advantage [35]. The potential is, therefore, clear.…”
Section: Dear Editormentioning
confidence: 99%
“…Therefore, an athlete wanting to compete against opponents of similar sizes will have no option other than to also engage in RWL procedures. This was made obvious by a combat athlete interviewed in the study by Petterson et al [35] who said "(…) if I wouldn't cut weight and everyone else does it, then I would be in trouble." This benefits those willing to take the risks and discomforts associated with RWL to the detriment of those unwilling to compromise their health by undertaking these stressful strategies;…”
Section: Dear Editormentioning
confidence: 99%
“…Taekwondo is one of the combat sports and can be described as a modern Olympic sport that required high intensity, to defeat the exponent using precise and quick kicks [1]. Among classical taekwondo competitions types (i.e.…”
Section: Introductionmentioning
confidence: 99%